The Relationship of Cadre Formation to Increasing Reproductive Health Knowledge at Miftahul Huda Tasikmalaya Islamic Boarding School - Arifah, Siti; Faridatulhuda, Sylvia; Dwihestie, Luluk Khusnul (Universitas 'Aisyiyah Yogyakarta, 2023)
Reproductive Health is a serious problem that is often experienced throughout the life cycle that has become a concern for the government. The formation of adolescent cadres is one form of extension of health workers in conveying reproductive health information. This study aims to determine the formation of adolescent cadres to increase reproductive health knowledge at Miftahul Huda Tasikmalaya Islamic Boarding School, West Java. This research design uses pre-experimental research with one group pretest-posttest design. The data collection technique in this study used a total sampling technique totaling 40 active adolescent students as administrators of Islamic boarding school health posts. The data collection tool in this study was a questionnaire that had been tested for validity and reliability with results of 0.850. The data collection method is carried out using primary data and secondary data. Data analysis using univariate and bivariate analysis with Wilcoxon test. The results of this study show that there is an influence of the formation of adolescent cadres by providing reproductive health counseling on increasing reproductive health knowledge at Miftahul Huda Islamic Boarding School, Manonjaya Tasikmalaya with Wilcoxon's statistical test producing P 0.000 < (p 0.05). There is a significant influence on increasing reproductive health knowledge at Miftahul Huda Islamic Boarding School, Manonjaya Tasikmalaya. It is hoped that adolescent cadres can pass on reproductive health information to their peers so that they can improve adolescent reproductive health.